2013
DOI: 10.3171/2012.10.jns121037
|View full text |Cite
|
Sign up to set email alerts
|

Timing of cranioplasty after decompressive craniectomy for ischemic or hemorrhagic stroke

Abstract: Complications rates for early cranioplasty (within 10 weeks of craniectomy) are similar to those encountered when cranioplasty is delayed, although the cohort size in this study was too small to state equivalence. Patients with a ventriculoperitoneal shunt are at higher risk for complications after cranioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 17 publications
3
87
1
2
Order By: Relevance
“…There is no study however, that examines the effect of timing on the clinical outcome of patients. In accordance with the available literature, timing does not influence complications, but there might be an advantage for early reinsertion (<3 months), especially with respect to the risk for infections [51,52,53,54,55,56]. Recently published studies reported an approximate overall complication rate of up to 35% [51,52].…”
Section: Surgical Treatmentsupporting
confidence: 61%
“…There is no study however, that examines the effect of timing on the clinical outcome of patients. In accordance with the available literature, timing does not influence complications, but there might be an advantage for early reinsertion (<3 months), especially with respect to the risk for infections [51,52,53,54,55,56]. Recently published studies reported an approximate overall complication rate of up to 35% [51,52].…”
Section: Surgical Treatmentsupporting
confidence: 61%
“…[6][7][8][9][10][11][14][15][16]18,20,21,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Several studies 19,32,[43][44][45][46] have reported an incidence of the syndrome of 1-15% and a time latency of 3-6 months from the DC to the onset of the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We found 253 potentially eligible articles of which 9 studies [5,6,8,9,27,28,32,34,41] were included. 244 non-pertinent titles or abstracts were excluded (Fig.…”
Section: Search Strategymentioning
confidence: 99%